Method for improving perovskite thin film forming quality and perovskite solar cell

Through the preparation of the perovskite film, the use of methylemine lead iodine and methyl iodine as the front-drive body, add inorganic salt and polyvy (4-ethylene pyrim) Tu and annealing treatment solves the problem of defects and impurities in existing technologies, and realizes the preparation and optimization of photoelectric performance of high -quality film.

CN119365043APending Publication Date: 2025-01-24SUZHOU GUANGSU TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411825694.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems in the preparation of high-quality perovskite films that it is difficult to accurately control the crystal structure and morphology of the film, resulting in a large number of defects and impurities in the film, affecting the photoelectric performance and stability.

Method used

By mixing methylamine lead iodide and formamidine lead iodide as perovskite precursor powders, adding solvent and inorganic salt powder, controlling the crystallization kinetics of the perovskite, and passivating defects with poly(4-vinylpyridine), Subsequently, spin coating and annealing treatments are performed to prepare high-quality perovskite films.

Benefits of technology

This method effectively regulates the crystal structure and appearance of the perovskite film, reduces the existence of defects and impurities, and significantly improves the photoelectric conversion efficiency and stability of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365043A_ABST
    Figure CN119365043A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the film forming quality of a perovskite thin film and a perovskite solar cell, and the method comprises the steps: taking methylamine lead iodine and formamidine lead iodine as perovskite precursor powder, mixing, adding a solvent, and stirring to obtain a precursor solution; adding inorganic salt powder into the precursor solution obtained in the step S1 to regulate and control crystallization of perovskite, and continuously stirring; s3, spin-coating a substrate with the forming solution obtained in the step S3 to obtain a perovskite thin film, and annealing and drying the perovskite thin film; by controlling the annealing temperature and time, the crystallization kinetics is further regulated and controlled, the rapid growth and ordered arrangement of the crystals are promoted, the defect and impurity concentration is reduced, the defect concentration is reduced, and the purity and uniformity of the crystals are improved; by controlling the annealing temperature and time, the crystallization kinetics is further regulated and controlled, the crystal quality and stability of the perovskite thin film are remarkably improved, the defect concentration is reduced, and the purity and uniformity of crystals are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid-state device using an organic material as an active part or using a combination of an organic material and other materials as an active part, and in particular to a method for improving the film-forming quality of a perovskite thin film and a perovskite solar cell, and is particularly suitable for sensing infrared radiation, light, shorter wavelength electromagnetic radiation or particle radiation; and is particularly suitable for the field of converting these radiation energies into electrical energy. Background Art

[0002] Perovskite films have the advantages of high photoelectric conversion efficiency, good stability and low cost, and are regarded as one of the mainstream materials for future solar cells. The crystal structure of perovskite materials enables them to efficiently absorb and convert sunlight to generate electricity. In addition, the preparation process of perovskite films is relatively simple and low-cost, which is conducive to large-scale production and application. However, in the preparation process of perovskite films, how to obtain high-quality films has always been the focus of research. High-quality perovskite films have the characteristics of large grain size, few defects and smooth surface, which are crucial to improving the photoelectric conversion efficiency and stability of solar cells.

[0003] Although perovskite films have many advantages, the existing technology still has some defects in the preparation of high-quality films. For example, traditional preparation methods often find it difficult to accurately control the crystal structure and morphology of the film, resulting in a large number of defects and impurities in the film. These defects and impurities can seriously affect the photoelectric properties and stability of the film. In addition, the existing technology also faces challenges in the preparation of large-area, uniform perovskite films. With the continuous development of solar cell technology, higher requirements are placed on the uniformity of films and large-area preparation capabilities. However, traditional preparation methods often find it difficult to meet these requirements, limiting the large-scale application of perovskite solar cells. Summary of the invention

[0004] The present invention overcomes the deficiencies of the prior art and provides a method for improving the film-forming quality of a perovskite thin film and a perovskite solar cell.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for improving the film quality of perovskite thin film, comprising the following steps:

[0006] S1: Mixing methylamine lead iodide and formamidinium lead iodide as perovskite precursor powders, adding a solvent, and stirring to obtain a precursor solution;

[0007] S2: adding inorganic salt powder to the precursor solution obtained in S1 to regulate the crystallization of perovskite, and continuously stirring to obtain a mixed solution of precursor solution-inorganic salt;

[0008] S3: adding poly(4-vinylpyridine) to the mixed solution obtained in S2 by dropping and stirring to passivate defects to obtain a molding solution;

[0009] S4: spin-coating the formed solution obtained in S3 onto a substrate to obtain a perovskite film, annealing the perovskite film, and drying it;

[0010] In a preferred embodiment of the present invention, in S1, the solvent is selected from a mixed solvent of dimethyl sulfoxide and dimethylformamide or a mixed solvent of dimethylacetamide and N-methylpyrrolidone, the mass fraction of the precursor solute is 10%-20%, and the ratio of the solvent to the precursor powder is 2-4:1.

[0011] In a preferred embodiment of the present invention, in S1, the stirring temperature is 60-80°C, the time is 2-4h, and the rotation speed is 300-500r / min.

[0012] In a preferred embodiment of the present invention, in S2, the inorganic salt is selected from one or more of ammonium chloride or ammonium bromide, and the amount of the inorganic salt added is 0.5%-5% of the mass of the precursor solute.

[0013] In a preferred embodiment of the present invention, in S2, the continuous stirring parameters are stirring temperature of 60-80°C, time of 1-2h, and rotation speed of 300-500r / min.

[0014] In a preferred embodiment of the present invention, in S3, the stirring parameters while dropping are 400-600 rpm, the dropping speed is 2-4 drops per second, the stirring time is 2-4 hours, and the addition amount of poly(4-vinylpyridine) is 0.1%-1% of the mass of the precursor solute.

[0015] In a preferred embodiment of the present invention, in S4, the substrate is selected from FTO glass or ITO glass, the spin coating speed is 2000-5000 rpm, and the spin coating time is 20-60 s.

[0016] In a preferred embodiment of the present invention, in S4, the annealing temperature is 100-150° C., and the time is 10-30 min; the drying temperature is 60-80° C., and the time is 1-2 h.

[0017] A perovskite solar cell comprises a perovskite film, wherein the perovskite film is prepared by the method for improving the film-forming quality of the perovskite film according to any one of claims 1 to 8.

[0018] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0019] (1) The present invention provides a method for improving the film quality of perovskite thin films and a perovskite solar cell. Through the ion exchange and interaction of inorganic salt additives, the crystallization kinetics of perovskite is effectively regulated, and the uniform nucleation and growth of crystals are promoted, thereby forming large-sized, high-quality grains. At the same time, certain ions in the inorganic salt can occupy defect sites in the perovskite, significantly reducing the defect concentration. The pyridine group in the poly(4-vinylpyridine) additive interacts with the uncoordinated Pb 2 + sites form coordination bonds, further passivating defects. By controlling the annealing temperature and time, the crystallization kinetics are further regulated, promoting the rapid growth and orderly arrangement of crystals, reducing the concentration of defects and impurities, significantly improving the crystal quality and stability of perovskite films, reducing defect concentration, and improving the purity and uniformity of crystals.

[0020] (2) The present invention provides a method for improving the film quality of perovskite thin film and a perovskite solar cell, wherein the crystallization kinetics are regulated by inorganic salt additives and poly (4-vinylpyridine) during the preparation of the perovskite thin film, the defects are passivated, and the crystal structure and morphology of the film are improved, and the defects and impurities in the film are further reduced by controlling the temperature during annealing, the recombination rate of carriers is reduced, and the photoelectric conversion efficiency of the film is significantly improved. Through the synergistic effect of inorganic salts, PVP additives and annealing, the photoelectric performance of the perovskite film is optimized, and the photoelectric conversion efficiency and stability are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 Schematic diagram comparing voltage-current density curves of perovskite solar cells according to preferred embodiments 1, 2 and 3 of the present invention;

[0023] Figure 2 Schematic diagram comparing voltage-current density curves of perovskite solar cells according to preferred embodiments 1, 4 and 5 of the present invention;

[0024] Figure 3 It is a schematic diagram comparing the voltage-current density curves of the perovskite solar cells according to the preferred embodiments 1, 6 and 7 of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0027] As shown in the figure, a method for improving the film quality of a perovskite thin film and a perovskite solar cell include: a method for improving the film quality of a perovskite thin film, including the following steps:

[0028] S1: Mixing methylamine lead iodide and formamidinium lead iodide as perovskite precursor powders, adding a solvent, and stirring to obtain a precursor solution;

[0029] In a preferred embodiment of the present invention, in S1, the solvent is selected from a mixed solvent of dimethyl sulfoxide and dimethylformamide or a mixed solvent of dimethylacetamide and N-methylpyrrolidone, and the mass fraction of the precursor solute is 10%-20%; in S1, the stirring temperature is 60-80°C, the time is 2-4h, the rotation speed is 300-500r / min, and the ratio of solvent to precursor powder is 2-4:1.

[0030] It should be noted that methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 10%-20%, and a mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1, added to the precursor powder, and stirred to dissolve the precursor powder. The stirring temperature is 60-80°C, the time is 2-4h, and the rotation speed is 300-500r / min to obtain a precursor solution.

[0031] It should also be noted that methylamine lead iodine has a relatively suitable bandgap width (about 1.5 eV), which matches the solar spectrum, and therefore has a high light absorption performance, and can absorb almost all visible light to the maximum extent; lead iodine with formamidinium also has excellent photoelectric properties, its band gap is close to the ideal value, and its thermal stability is higher than that of lead iodine with methylamine; however, during the preparation process, the molecular structure of lead iodine with methylamine and lead iodine with formamidinium is easily affected by external factors such as solvent, temperature, and humidity, and this change will cause the molecules in the film to be arranged irregularly, thereby affecting the uniformity and stability of the film, and in the process of using a solvent for dissolution, the solubility and dissolution rate of lead iodine with methylamine and lead iodine with formamidinium are different, which will cause the molecular concentration in the precursor solution to be unevenly distributed. This uneven concentration distribution may cause the thickness and uniformity of the film to be affected during the spin coating process, thereby affecting the quality stability of the film; there are strong interactions between lead iodine with methylamine and lead iodine with formamidinium, such as hydrogen bonds, ionic bonds, etc. These interaction forces may cause irregular arrangement of molecules during the crystallization process, resulting in more defects and vacancies, thereby reducing the crystallinity of the film.

[0032] S2: adding inorganic salt powder to the precursor solution obtained in S1 to regulate the crystallization of perovskite, and continuously stirring to obtain a mixed solution of precursor solution-inorganic salt;

[0033] In a preferred embodiment of the present invention, in S2, the inorganic salt is selected from one or more of ammonium chloride or ammonium bromide, and the amount of inorganic salt added is 0.5%-5% of the mass of the precursor solute; in S2, the continuous stirring parameters are stirring temperature of 60-80°C, time of 1-2h, and rotation speed of 300-500r / min.

[0034] It should be noted that ammonium chloride powder is selected as the inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 0.5%-5% of the mass of the precursor solute, and stirred at 60-80°C for 1-2 hours at a speed of 300-500r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0035] It should also be noted that some ions in the inorganic salt additive can exchange with ions in the perovskite component. Specifically, when ammonium chloride is selected as the inorganic salt, the Na + and Cl - ions can be exchanged with ions in the perovskite component. Specifically, during the preparation of the perovskite film, the Cl - ions will interact with the X-site ions in the perovskite (such as I - ) exchange occurs, and Na + Ions may be associated with A-site ions (such as MA + , FA+ This ion exchange not only changes the composition and structure of the perovskite, but may also affect the crystallization kinetics of the perovskite. By adjusting the amount of ammonium chloride added, the degree of ion exchange can be precisely controlled, thereby optimizing the crystal structure and properties of the perovskite film.

[0036] Moreover, ammonium chloride can interact with ions in the perovskite component through surface adsorption and coordination. Specifically, during the preparation of perovskite film, ions or molecules in ammonium chloride will be adsorbed on the surface of perovskite crystals and bind to Pb in perovskite through coordination bonds. 2+ Ion binding. This surface adsorption and coordination effect helps stabilize the crystal structure of perovskite and prevents it from agglomerating or decomposing during the preparation process. At the same time, this interaction can also regulate the growth rate and growth direction of the crystal, thereby obtaining a better quality crystal structure.

[0037] When ammonium chloride is used as an inorganic salt, the crystallization dynamics of perovskite can be regulated. Specifically, ammonium chloride can act as a nucleation center to promote uniform nucleation and preferential orientation growth of perovskite films. During the preparation of perovskite films, ions or molecules in ammonium chloride can act as "seeds" for crystal nuclei, guiding the growth of perovskite crystals in a specific direction. This preferential orientation growth helps to form large-sized, high-quality grains, thereby improving the performance of perovskite films. As a carrier of perovskite materials, ammonium chloride can enhance the stability of perovskite films and prevent them from decomposing and degrading under external conditions such as light and humidity.

[0038] S3: adding poly(4-vinylpyridine) to the mixed solution obtained in S2 by dropping and stirring to passivate defects to obtain a molding solution;

[0039] In a preferred embodiment of the present invention, in S3, the stirring parameters while dropping are 400-600 rpm, the dropping speed is 2-4 drops per second, the stirring time is 2-4 hours, and the addition amount of poly(4-vinylpyridine) is 0.1%-1% of the mass of the precursor solute.

[0040] It should be noted that poly(4-vinylpyridine) is added to the mixed solution of the precursor solution and the inorganic salt by dropping and stirring, wherein the parameters of dropping and stirring are 400-600 rpm, the dropping speed is 2-4 drops per second, the stirring time is 2-4 hours, and the amount of poly(4-vinylpyridine) added is 0.1%-1% of the mass of the precursor solute. During the dropping process, the poly(4-vinylpyridine) molecules gradually enter the perovskite precursor solution and react with the Pb 2+ ions interact with other components, and continuous stirring promotes the mixing and interaction between poly(4-vinylpyridine) molecules and the components in the perovskite precursor solution, so that the poly(4-vinylpyridine) molecules can more fully contact the Pb 2 + ions and other defect sites, thereby more effectively forming coordination bonds and passivating defects.

[0041] It should also be noted that in the precursor solution, due to reasons such as temperature fluctuations and solvent evaporation, atoms or molecules fail to fully occupy their proper positions, leaving vacancies in the crystal structure or molecular chain. These vacancies exist in the form of single atoms or in the form of regions composed of multiple atoms. Vacancy defects will destroy the uniformity and integrity of the precursor solution, thereby affecting its subsequent performance and application. In addition, in the precursor solution, due to incomplete reaction or molecular chain breakage, the valence electrons of some atoms or molecular fragments fail to fully pair, thus forming unsaturated bonds. These unsaturated bonds have high energy and reactivity, and are easy to interact with other atoms or molecules, thereby initiating a series of chemical reactions. Dangling bond defects will reduce the stability of the precursor solution and may cause its performance to deteriorate. The poly(4-vinylpyridine) molecule is composed of vinyl and pyridine rings. The vinyl gives it polymer properties, while the pyridine ring is a functional group with aromaticity and polarity. The nitrogen atom on the pyridine ring has a pair of lone pairs of electrons, which makes the poly(4-vinylpyridine) molecule have a certain polarity. In the precursor solution, due to various factors in the preparation process, defect sites with vacancies and dangling bonds will be formed. These defect sites have unpaired electrons, unsaturated bonds or different chemical properties, thus becoming potential targets for poly(4-vinylpyridine) molecules to interact with them. A coordination bond is a special covalent bond in which one atom (ligand) provides a lone pair of electrons and another atom (central atom or ion) provides an empty orbital. Here, the nitrogen atom on the pyridine ring in the poly(4-vinylpyridine) molecule acts as a ligand, while the cation in the defect site or the atom with an empty orbital acts as the central atom. When the poly(4-vinylpyridine) molecule is added to the precursor solution, the nitrogen atom on its pyridine ring will approach the defect site. The defect site has an empty orbital or a cation that can accept a lone pair of electrons, and the nitrogen atom will provide its lone pair of electrons to form a coordination bond with it. The formation of this coordination bond stabilizes the defect site and reduces its reactivity. A hydrogen bond is an intermolecular interaction force that occurs between atoms with high electronegativity (such as nitrogen, oxygen, and fluorine) and hydrogen atoms. Here, the nitrogen atom of the pyridine ring in the poly(4-vinylpyridine) molecule forms a hydrogen bond with a hydrogen atom in a defect site (such as a hydrogen atom on a dangling bond or a hydrogen atom on an impurity atom). When the poly(4-vinylpyridine) molecule approaches a defect site, the nitrogen atom on its pyridine ring can form a hydrogen bond with a hydrogen atom in the defect site. The formation of this hydrogen bond further stabilizes the defect site and helps anchor the poly(4-vinylpyridine) molecule at the defect position. By forming a coordination bond or a hydrogen bond, the poly(4-vinylpyridine) molecule can effectively recognize and cover the defect site in the precursor solution. These interactions not only stabilize the defect site, but also reduce the subsequent chemical reactions or physical changes that may be triggered by it.In addition, the long chain structure of poly(4-vinylpyridine) molecules allows them to move and intersperse freely in the solution, thus enabling more effective coverage and repair of defective areas. The pyridine groups in poly(4-vinylpyridine) contain lone electron pairs that can bind to uncoordinated Pb in the perovskite film. 2+ The empty 6p orbital of the ion forms a stable coordination bond. From a molecular level, the coordination bond is formed by the pyridine ring nitrogen atom in the poly(4-vinylpyridine) molecule providing a lone electron pair to bind to the Pb 2+ The empty orbitals of the ions interact with each other to form a new chemical bonding state.

[0042] Poly(4-vinylpyridine) molecules have a specific chemical structure and polarity. The nitrogen atom on the pyridine ring can react with the metal ions (such as Pb) in the perovskite precursor molecules. 2+ ) interactions, including coordination bonds, hydrogen bonds, and van der Waals forces, which together constitute the connecting bridge between poly (4-vinyl pyridine) and perovskite precursor molecules. In the preparation process of perovskite film, poly (4-vinyl pyridine) molecules may first form a certain aggregation state or ordered structure in the precursor solution. These ordered structures provide a "template" for the growth of perovskite crystals, that is, a framework with a specific shape and orientation. Under the action of the template effect, the perovskite precursor molecules will be orderly arranged and stacked along the template structure formed by the poly (4-vinyl pyridine) molecules. This ordered structure The arrangement and stacking lead to the preferential growth of perovskite crystals in a specific direction, that is, directional growth. The template effect not only guides the directional growth of the crystals, but also promotes the increase of grain size and the optimization of morphology. Under the guidance of the template, the perovskite precursor molecules are more likely to form larger nuclei and form crystals with regular morphology through a continuous growth process. Since the crystals grow in an orderly manner according to the template, the formation of defects is limited. In addition, the functional groups in the poly(4-vinylpyridine) molecules interact with the defect sites in the perovskite precursor molecules, thereby further passivating these defects.

[0043] In the perovskite precursor solution, the functional groups in the poly(4-vinylpyridine) molecules (such as the nitrogen atoms on the pyridine ring) carry partial negative charges, while the ammonium ions (NH 4 + ) and chloride ions (Cl -) carry positive and negative charges respectively. The functional groups in the poly(4-vinylpyridine) molecule can undergo ion exchange reactions with the ions in ammonium chloride, that is, the negatively charged part of the poly(4-vinylpyridine) molecule combines with the ammonium ions, while the chloride ions may be released into the solution or combined with other cations. This ion exchange reaction will change the charge distribution and ion concentration of the perovskite precursor solution, thereby affecting the growth process and final structure of the crystal; hydrogen bonds may form between the pyridine ring nitrogen atoms in the poly(4-vinylpyridine) molecule and the hydrogen atoms in ammonium chloride. Hydrogen bonds are a strong intermolecular interaction force that can guide the directional growth of crystals by affecting the arrangement and orientation of molecules. The formation of hydrogen bonds not only enhances the interaction between the poly(4-vinylpyridine) molecule and the ammonium chloride molecule, but also stabilizes the crystal structure by affecting the interaction between the perovskite precursor molecules.

[0044] In the perovskite precursor solution, the interaction between poly(4-vinylpyridine) and ammonium chloride stabilizes the crystal structure at the molecular level by changing the charge distribution and ion concentration of the solution. Specifically, the functional groups in the poly(4-vinylpyridine) molecule (such as the nitrogen atom on the pyridine ring) may have partial negative charges, which can react with the ammonium ions (NH4+) in ammonium chloride. 4 + ) interact with each other to form a charge-balanced structure. This charge balance helps to reduce the number of free ions in the solution, thereby reducing the charge repulsion during crystal growth and making the crystal structure more stable; the chloride ions (Cl-) and ammonium ions in ammonium chloride can form an ion shielding layer around the poly(4-vinylpyridine) molecules, which can block the interference of other ions in the solution on crystal growth and protect the crystal structure from the influence of the external environment; the interaction between poly(4-vinylpyridine) and ammonium chloride can also passivate defect sites in the crystal through chemical reactions. For example, the functional groups in the poly(4-vinylpyridine) molecules may coordinate or hydrogen bond with the defect sites in the crystal, thereby stabilizing these defect sites and reducing defects and dislocations in the crystal.

[0045] The hydrogen bond interaction that may be formed between poly(4-vinylpyridine) and ammonium chloride guides the directional growth of perovskite crystals at the molecular level. Specifically, hydrogen bonds can be formed between the pyridine ring nitrogen atoms in the poly(4-vinylpyridine) molecule and the hydrogen atoms in the ammonium chloride. These hydrogen bonds play a guiding role in the crystal growth process, guiding the perovskite precursor molecules to arrange and stack in a specific direction, thereby forming a directional growth crystal; the interaction between poly(4-vinylpyridine) and ammonium chloride forms a template structure, which provides a "framework" for the growth of perovskite crystals. Within this framework, the perovskite precursor molecules will be arranged and stacked in an orderly manner according to the shape and orientation of the template, thereby guiding the directional growth of the crystal.

[0046] The interaction between poly(4-vinylpyridine) and ammonium chloride affects the size of perovskite grains at the molecular level. Specifically, the interaction between poly(4-vinylpyridine) and ammonium chloride affects the grain size by regulating the crystal growth rate. Poly(4-vinylpyridine) molecules may be adsorbed on the crystal surface, slowing down or accelerating the crystal growth rate, thereby affecting the grain size. During the crystal nucleation process, the interaction between poly(4-vinylpyridine) and ammonium chloride controls the grain size by affecting the nucleation rate and the stability of the nucleus.

[0047] S4: spin-coating the formed solution obtained in S3 onto a substrate to obtain a perovskite film, annealing the perovskite film, and drying it;

[0048] In a preferred embodiment of the present invention, in S4, the substrate is selected from one of FTO glass or ITO glass, the spin coating speed is 2000-5000rpm, and the spin coating time is 20-60s; in S4, the annealing temperature is 100-150°C, and the time is 10-30min; the drying temperature is 60-80°C, and the time is 1-2h.

[0049] It should be noted that the obtained forming solution is spin-coated on the FTO glass substrate using a spin coater, the spin coating speed is 2000-5000rpm, the spin coating time is 20-60s, and the spin-coated perovskite film is placed on a heating plate for annealing. The annealing temperature is 100-150°C and the time is 10-30min. After the annealing is completed, the perovskite film is removed, naturally cooled to room temperature, and dried in a drying oven at a drying temperature of 60-80°C for 1-2 hours.

[0050] During the annealing process, as the temperature rises, the perovskite precursor molecules (including complexes formed with inorganic salts such as ammonium chloride and poly (4-vinylpyridine)) begin to obtain sufficient energy to rearrange. This rearrangement helps to eliminate the disordered arrangement between molecules and promote the orderly growth of crystals. As the crystal nuclei are rapidly formed and grow stably, a high-quality crystal structure is obtained. In this process, the additives interact with the perovskite molecules through their functional groups, further promoting the orderly arrangement and growth of the crystals. Rapid annealing also helps to eliminate defects in the film, such as vacancies and interstitial atoms. These defects will be repaired by molecular rearrangement and diffusion during the annealing process, thereby improving the purity and integrity of the crystal.

[0051] As the temperature rises during rapid annealing, impurity atoms or molecules in the film can obtain enough energy to migrate. These impurities will be expelled to the surface of the film or wrapped in tiny defects formed inside the crystal, thereby reducing their impact on the crystal structure and performance. Similar to defect elimination, rapid annealing can also promote the defect repair process. Through molecular rearrangement and diffusion, some smaller defects may be repaired into more stable structures, thereby reducing the defect concentration. During the annealing process, additives will decompose or volatilize, further reducing the impurity concentration in the film. The decomposition products of these additives may escape the film in the form of gas, leaving a purer perovskite crystal structure.

[0052] A perovskite solar cell comprises a perovskite film, wherein the perovskite film is prepared by the method for improving the film-forming quality of the perovskite film according to any one of claims 1 to 8.

[0053] Embodiment 1:

[0054] Methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 15%. A mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1 and added to the precursor powder, and the ratio of the solvent to the precursor powder is 3:1. The precursor powder is dissolved by stirring at a temperature of 70°C, a time of 3 hours, and a rotation speed of 400 r / min to obtain a precursor solution.

[0055] Ammonium chloride powder is used as an inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 2.5% of the mass of the precursor solute, and stirred at 70°C for 1.5 hours at a speed of 400r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0056] Poly(4-vinylpyridine) was added to the precursor solution-inorganic salt mixed solution by dropping and stirring, wherein the dropping and stirring parameters were 500 rpm, the dropping speed was 3 drops per second, the stirring time was 2.5 hours, and the addition amount of poly(4-vinylpyridine) was 0.5% of the mass of the precursor solute.

[0057] The obtained forming solution was spin-coated on the FTO glass substrate using a spin coater at a speed of 3500 rpm for 40 s. The spin-coated perovskite film was placed on a heating plate for annealing at a temperature of 120°C for 20 min. After the annealing was completed, the perovskite film was removed, cooled naturally to room temperature, and dried in a drying oven at 70°C for 1.5 hours.

[0058] Embodiment 2:

[0059] Methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 15%. A mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1, added to the precursor powder, and the ratio of the solvent to the precursor powder is 1:1. The precursor powder is dissolved by stirring at a temperature of 70°C, a time of 3 hours, and a rotation speed of 400 r / min to obtain a precursor solution.

[0060] Ammonium chloride powder is used as an inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 2.5% of the mass of the precursor solute, and stirred at 70°C for 1.5 hours at a speed of 400r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0061] Poly(4-vinylpyridine) was added to the precursor solution-inorganic salt mixed solution by dropping and stirring, wherein the dropping and stirring parameters were 500 rpm, the dropping speed was 3 drops per second, the stirring time was 2.5 hours, and the addition amount of poly(4-vinylpyridine) was 0.5% of the mass of the precursor solute.

[0062] The obtained forming solution was spin-coated on the FTO glass substrate using a spin coater at a speed of 3500 rpm for 40 s. The spin-coated perovskite film was placed on a heating plate for annealing at a temperature of 120°C for 20 min. After the annealing was completed, the perovskite film was removed, cooled naturally to room temperature, and dried in a drying oven at 70°C for 1.5 hours.

[0063] Embodiment 3

[0064] Methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 15%. A mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1 and added to the precursor powder, and the ratio of the solvent to the precursor powder is 5:1. The precursor powder is dissolved by stirring at a temperature of 70°C, a time of 3 hours, and a rotation speed of 400 r / min to obtain a precursor solution.

[0065] Ammonium chloride powder is used as an inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 2.5% of the mass of the precursor solute, and stirred at 70°C for 1.5 hours at a speed of 400r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0066] Poly(4-vinylpyridine) was added to the precursor solution-inorganic salt mixed solution by dropping and stirring, wherein the dropping and stirring parameters were 500 rpm, the dropping speed was 3 drops per second, the stirring time was 2.5 hours, and the addition amount of poly(4-vinylpyridine) was 0.5% of the mass of the precursor solute.

[0067] The obtained forming solution was spin-coated on the FTO glass substrate using a spin coater at a speed of 3500 rpm for 40 s. The spin-coated perovskite film was placed on a heating plate for annealing at a temperature of 120°C for 20 min. After the annealing was completed, the perovskite film was removed, cooled naturally to room temperature, and dried in a drying oven at 70°C for 1.5 hours.

[0068] Embodiment 4:

[0069] Methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 15%. A mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1 and added to the precursor powder, and the ratio of the solvent to the precursor powder is 3:1. The precursor powder is dissolved by stirring at a temperature of 70°C, a time of 3 hours, and a rotation speed of 400 r / min to obtain a precursor solution.

[0070] Ammonium chloride powder is used as an inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 2.5% of the mass of the precursor solute, and stirred at 70°C for 1.5 hours at a speed of 400r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0071] Poly(4-vinylpyridine) was added to the precursor solution-inorganic salt mixed solution by dropping and stirring, wherein the dropping and stirring parameters were 500 rpm, the dropping speed was 3 drops per second, the stirring time was 2.5 hours, and the addition amount of poly(4-vinylpyridine) was 3% of the mass of the precursor solute.

[0072] The obtained forming solution was spin-coated on the FTO glass substrate using a spin coater at a speed of 3500 rpm for 40 s. The spin-coated perovskite film was placed on a heating plate for annealing at a temperature of 120°C for 20 min. After the annealing was completed, the perovskite film was removed, cooled naturally to room temperature, and dried in a drying oven at 70°C for 1.5 hours.

[0073] Embodiment 5

[0074] Methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 15%. A mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1 and added to the precursor powder, and the ratio of the solvent to the precursor powder is 3:1. The precursor powder is dissolved by stirring at a temperature of 70°C, a time of 3 hours, and a rotation speed of 400 r / min to obtain a precursor solution.

[0075] Ammonium chloride powder is used as an inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 2.5% of the mass of the precursor solute, and stirred at 70°C for 1.5 hours at a speed of 400r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0076] Poly(4-vinylpyridine) was added to the mixed solution of the precursor solution-inorganic salt by dropping and stirring, wherein the dropping and stirring parameters were 500 rpm, the dropping speed was 3 drops per second, the stirring time was 2.5 hours, and the addition amount of poly(4-vinylpyridine) was 0.1% of the mass of the precursor solute.

[0077] The obtained forming solution was spin-coated on the FTO glass substrate using a spin coater at a speed of 3500 rpm for 40 s. The spin-coated perovskite film was placed on a heating plate for annealing at a temperature of 120°C for 20 min. After the annealing was completed, the perovskite film was removed, cooled naturally to room temperature, and dried in a drying oven at 70°C for 1.5 hours.

[0078] Embodiment six:

[0079] Methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 15%. A mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1 and added to the precursor powder, and the ratio of the solvent to the precursor powder is 3:1. The precursor powder is dissolved by stirring at a temperature of 70°C, a time of 3 hours, and a rotation speed of 400 r / min to obtain a precursor solution.

[0080] Ammonium chloride powder is used as an inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 2.5% of the mass of the precursor solute, and stirred at 70°C for 1.5 hours at a speed of 400r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0081] Poly(4-vinylpyridine) was added to the precursor solution-inorganic salt mixed solution by dropping and stirring, wherein the dropping and stirring parameters were 500 rpm, the dropping speed was 3 drops per second, the stirring time was 2.5 hours, and the addition amount of poly(4-vinylpyridine) was 0.5% of the mass of the precursor solute.

[0082] The obtained forming solution was spin-coated on the FTO glass substrate using a spin coater at a spin coating speed of 3500 rpm and a spin coating time of 40 s. The spin-coated perovskite film was placed on a heating plate for annealing at a temperature of 200°C for 20 min. After annealing, the perovskite film was removed, naturally cooled to room temperature, and dried in a drying oven at a drying temperature of 70°C for 1.5 hours.

[0083] Embodiment 7

[0084] Methylamine lead iodine and formamidine lead iodine are mixed as perovskite powder precursors, wherein the mass fraction of the precursor powder is 15%. A mixed liquid of dimethyl sulfoxide and dimethylformamide is added to the precursor powder as a solvent, and dimethyl sulfoxide and dimethylformamide are mixed in a ratio of 1:1 and added to the precursor powder, and the ratio of the solvent to the precursor powder is 3:1. The precursor powder is dissolved by stirring at a temperature of 70°C, a time of 3 hours, and a rotation speed of 400 r / min to obtain a precursor solution.

[0085] Ammonium chloride powder is used as an inorganic salt, and the inorganic salt additive powder is slowly added to the precursor solution. The amount of inorganic salt added is 2.5% of the mass of the precursor solute, and stirred at 70°C for 1.5 hours at a speed of 400r / min to ensure its uniform dispersion to obtain a mixed solution of precursor solution-inorganic salt.

[0086] Poly(4-vinylpyridine) was added to the precursor solution-inorganic salt mixed solution by dropping and stirring, wherein the dropping and stirring parameters were 500 rpm, the dropping speed was 3 drops per second, the stirring time was 2.5 hours, and the addition amount of poly(4-vinylpyridine) was 0.5% of the mass of the precursor solute.

[0087] The obtained forming solution was spin-coated on the FTO glass substrate using a spin coater at a spin coating speed of 3500 rpm for 40 s. The spin-coated perovskite film was placed on a heating plate for annealing at a temperature of 80°C for 20 min. After the annealing was completed, the perovskite film was removed, naturally cooled to room temperature, and dried in a drying oven at a drying temperature of 70°C for 1.5 hours.

[0088] The perovskite solar cell prepared by the perovskite film prepared in the above-mentioned Examples 1 to 4 is tested for filling factor. Specifically, a solar cell IV tester is used to connect the perovskite solar cell to the circuit of the tester to ensure that the connection is firm and the contact is good. The tester is started to perform an IV (current-voltage) test. The tester will automatically measure and record the open circuit voltage, short circuit current and current values ​​of the solar cell at different voltages, such as Figure 1 As shown, it is a schematic diagram of the comparison of the voltage-current density curves of the perovskite solar cells of Examples 1 to 4, wherein the various data obtained by the detection are specifically shown in Table 1.

[0089]

[0090]

[0091] Combined with Example 1, Example 2 and Example 3 in Table 1 and Figure 1 It can be seen that in the process of using a mixed liquid of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) as a solvent to dissolve the precursor powder to prepare a perovskite film, when the amount of solvent added is too much, the concentration of the precursor solution will decrease, thereby slowing down the crystallization rate of the film. When the solution concentration is too low, it means that the distribution of the precursor molecules in the solvent becomes sparse, the distance between molecules increases, and the interaction between the precursor molecules weakens. This weakening of the interaction makes it difficult for the precursor molecules to form a compact and ordered structure, thereby increasing the difficulty of forming a stable crystal structure, that is, the weakening of the intermolecular interaction and the obstruction of the crystallization process, and the energy required to form a stable crystal structure increases. This means that under the same conditions, the difficulty of forming a high-quality perovskite film increases, which is equivalent to increasing the formation energy, making the crystallization process of the film more difficult. In addition, too much solvent will cause the film to shrink unevenly during the drying and annealing process, and it is easy to produce cracks and pinhole structures. These defects will seriously affect the optoelectronic properties and stability of the film. If the amount of solvent added is too little, the precursor solution will be too viscous and difficult to evenly coat on the substrate, which will make the thickness and uniformity of the film difficult to control. It will also increase the formation energy and affect the growth of crystals. If the amount of solvent added is too little, the precursor molecules will aggregate and crystallize prematurely during the solvent evaporation process, forming an uneven particle distribution, which will affect the optical and electrical properties of the film.

[0092] Combined with Example 1, Example 4 and Example 5 in Table 1 and Figure 2 It can be seen

[0093] Poly(4-vinylpyridine) molecules have specific functional groups and structures. When the amount added is too high, these molecules will exist in a large number in the perovskite precursor solution, and thus these molecules will occupy too many perovskite crystal growth sites during the crystallization process. It is difficult for the perovskite precursor molecules to find suitable positions for orderly arrangement during crystallization, which leads to the obstruction of the normal growth of the crystal. The crystallization process of the film becomes more complicated and slow, and the formation energy increases.

[0094] Moreover, due to the obstruction of poly (4-vinylpyridine) molecules, it is difficult for perovskite crystals to form a complete and ordered structure, resulting in a large number of defects and irregular structures in the film, such as vacancies and interstitial atoms, which makes the crystalline structure of the film incomplete. With the excess of poly (4-vinylpyridine), the growth space of perovskite grains will be limited, thereby causing the grain size to decrease, thereby affecting the optical properties, electrical properties and mechanical properties of the film.

[0095] Too high a content of poly(4-vinylpyridine) will also cause the film surface to become too rough, forming an uneven morphology, which will affect the light absorption and charge transfer performance of the film, thereby reducing the photoelectric conversion efficiency of the solar cell. If the amount of poly(4-vinylpyridine) added is too low, it will not be able to effectively passivate the defects in the perovskite film and will not be able to fully play its role in improving the film performance. This will also increase the formation energy, causing the crystal quality and stability of the film to decrease.

[0096] Combined with Example 1, Example 6 and Example 7 in Table 1 and Figure 3 It can be seen that when the annealing temperature is too high, the growth and diffusion process of the crystal will be accelerated, which will cause excessive crystal growth or unnecessary phase change. This will increase the formation energy, making it difficult to control the crystal quality of the film. Too high an annealing temperature will also cause the organic components in the film to decompose or volatilize, resulting in pores and defects. These defects will seriously affect the photoelectric properties and stability of the film. If the annealing temperature is too low, it will not be able to effectively promote the growth and orderly arrangement of the crystal. This will lead to an incomplete crystal structure in the film and increase the formation energy. Too low an annealing temperature can also lead to the presence of solvent residues and incompletely reacted precursor molecules in the film. These residues will seriously affect the purity and performance of the film.

[0097] In summary, the amount of solvent added, the amount of PVP added, and the annealing temperature interact with each other and jointly affect the formation and performance of perovskite films. When the amount of solvent added is too much and the amount of PVP added is too low, the film may not be able to form a stable crystal structure, and the surface roughness increases. At the same time, if the annealing temperature is too low, it cannot effectively promote the growth and orderly arrangement of crystals, further reducing the performance of the film. Conversely, if the amount of solvent added is too little and the amount of PVP added is too high, the film thickness may be uneven and the surface may be too rough. At the same time, if the annealing temperature is too high, the organic components in the film may decompose or volatilize, resulting in pores and defects.

[0098] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for improving the film quality of perovskite thin film, characterized in that: The following steps are involved: S1: Mixing methylamine lead iodide and formamidinium lead iodide as perovskite precursor powders, adding a solvent, and stirring to obtain a precursor solution; S2: adding inorganic salt powder to the precursor solution obtained in S1 to regulate the crystallization of perovskite, and continuously stirring to obtain a mixed solution of precursor solution-inorganic salt; S3: adding poly(4-vinylpyridine) to the mixed solution obtained in S2 by dropping and stirring to passivate defects to obtain a molding solution; S4: spin-coating the formed solution obtained in S3 onto a substrate to obtain a perovskite film, annealing the perovskite film, and drying it.

2. A method for improving the film quality of perovskite thin film according to claim 1, characterized in that: In S1, the solvent is selected from a mixed solvent of dimethyl sulfoxide and dimethylformamide or a mixed solvent of dimethylacetamide and N-methylpyrrolidone, the mass fraction of the precursor solute is 10%-20%, and the ratio of the solvent to the precursor powder is 2-4:

1.

3. The method for improving the film quality of perovskite thin film according to claim 1, characterized in that: In the S1, the stirring temperature is 60-80°C, the time is 2-4h, and the rotation speed is 300-500r / min.

4. The method for improving the film quality of perovskite thin film according to claim 1, characterized in that: In the step S2, the inorganic salt is selected from one or more of ammonium chloride and ammonium bromide, and the amount of the inorganic salt added is 0.5% to 5% of the mass of the precursor solute.

5. The method for improving the film quality of perovskite thin film according to claim 1, characterized in that: In S2, the continuous stirring parameters are stirring temperature of 60-80°C, time of 1-2h, and rotation speed of 300-500r / min.

6. The method for improving the film quality of perovskite thin film according to claim 1, characterized in that: In S3, the stirring parameters for dropping and adding are 400-600 rpm, the dropping speed is 2-4 drops per second, the stirring time is 2-4 hours, and the added amount of poly(4-vinylpyridine) is 0.1%-1% of the mass of the precursor solute.

7. The method for improving the film quality of perovskite thin film according to claim 1, characterized in that: In S4, the substrate is selected from FTO glass or ITO glass, the spin coating speed is 2000-5000 rpm, and the spin coating time is 20-60 s.

8. The method for improving the film quality of perovskite thin film according to claim 1, characterized in that: In the S4, the annealing temperature is 100-150°C for 10-30 minutes; the drying temperature is 60-80°C for 1-2 hours.

9. A perovskite solar cell, based on a method for improving the film quality of a perovskite thin film and a perovskite solar cell according to any one of claims 1 to 8, characterized in that: Including perovskite films.

10. A perovskite solar cell according to claim 9, characterized in that: The perovskite film is prepared by the method for improving the film-forming quality of the perovskite film according to any one of claims 1 to 8.